G513 Seizure management in end-of-life care for children. (24th May 2017) - Harris, N; Baba, M; Beringer, A; Mellor, C; Rogers, R; Taylor, K; Sharples, PM
Abstract : Background: Controlling seizures in children approaching death is often challenging. The evidence base to guide best practice is limited. We compared current practice in our region against the guidance for seizure management produced by the Association of Paediatric Palliative Medicine (APPM), seeking to identify any difficulties, barriers, and areas for improvement in symptom control. Methods: Retrospective case note review of episodes of challenging seizure management in children receiving end-of-life care over a ten year period (2006–2015). Results: We identified and reviewed eighteen cases. Six (33%) had a malignancy, eight (44%) had a progressive neurodegenerative condition, and four (22%) had a static neurological condition with associated epilepsy. Fifteen (83%) had seizures during their final admission/care episode, and the remaining three had had status epilepticus previously and were felt to be at high risk of recurrence. Thirteen (72%) died in their local hospice, four (22%) at home, and one (6%) in hospital. Seventeen (94%) involved the use of subcutaneous or intravenous midazolam infusion, for a mean of eleven days (range 3–27). There was a wide range of starting doses of midazolam, and 9/17 (53%) received final doses in excess of APPM dose recommendations. Six individuals (33%) received subcutaneous phenobarbital infusions, with four of these (67%) receiving final doses in excess of APPM dose recommendations. Plans for adjustments of infusion rates, maximal doses, or alternative approaches should treatment fail, were inconsistent. In 17/18 (94%) cases seizures were successfully controlled in the days or hours before the child died, but this was sometimes a prolonged process. Fear of apnoea or over-sedation were the main barriers to prompt symptom control. Staff found the experience of managing seizures at end-of-life challenging and stressful. Conclusions: Pharmacological approaches to seizure management in end-of-life care are variable, often exceeding dose recommendations. Despite this, safe and effective seizure control was reported to be possible in all settings. Best-practice management guidance should be developed to support improved care and to increase staff confidence in this area. Project funded by Health Education England